Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Bailiff Robert Shinn calling en banc court session to order